THE EFFECT OF STRESS ON JOB PERFORMANCE AMONG HEALTHCARE EMPLOYEES IN SOUTH PUNJAB (Journal of Medical & Health Sciences Review, 2025)
Background: Stress among healthcare professionals is a critical issue that can significantly impair job performance and patient care quality. In South Punjab, healthcare workers face high-pressure environments due to heavy workloads, administrative burdens, and interpersonal challenges. Burnout, often resulting from prolonged stress, further exacerbates these issues by reducing job satisfaction and increasing absenteeism and turnover.Objective: This study aims to investigate the relationship between stress and employee performance in the healthcare sector of South Punjab, with a focus on burnout as a mediating factor. The research seeks to inform strategies for improving mental well-being and enhancing service delivery within the region’s healthcare system.Methods: A quantitative research design was employed, utilizing a structured questionnaire to collect data from 398 healthcare employees across hospitals, clinics, and health centers in South Punjab. The Perceived Stress Scale (PSS) and Maslach Burnout Inventory (MBI) were used to assess stress and burnout levels, respectively. Stratified random sampling ensured representation across different types of healthcare facilities. Data were analyzed using SPSS through reliability analysis, descriptive statistics, correlation, and regression analyses.Results: Cronbach’s alpha values for stress (0.81), burnout (0.92), and employee performance (0.84) indicated strong internal consistency. Mean stress level was relatively high (M = 3.71), while burnout (M = 3.15) and performance (M = 3.32) scores were lower. Skewness and kurtosis suggested non-normal distributions requiring careful interpretation. Stress showed a moderate positive correlation with burnout (r = 0.38) and a strong negative correlation with employee performance (r = –0.52). Burnout had an even stronger negative correlation with performance (r = –0.77). Burnout was found to partially mediate the relationship between stress and employee performance. Burnout increased under higher stress, which in turn reduced job performance.Conclusion: The findings highlight the detrimental impact of stress and burnout on healthcare workers’ performance in South Punjab. Burnout plays a significant role in mediating this relationship, underscoring the need for targeted interventions such as stress management programs, wellness initiatives, and performance enhancement strategies. These measures are essential for improving workforce resilience, job satisfaction, and ultimately, the quality of patient care in the region.